Preparation of Agarose-glucan Protein Drug Delivery for Anti-tumor Necrosis Factor - Bao Ngoc, Nguyen; Thi Ly, Do; Derouet, Esther; Huu Tuan Dung, Nguyen; Thanh Tung, Nguyen; Thi Phuong Linh, Nguyen; Hoang Nam, Nguyen; Minh Hieu, Nguyen; Dinh Thang, Nguyen; Thi Van Anh, Nguyen; Thi Thu Huong, Pham (VNU Journal of Science: Natural Sciences and Technology, 2018)
Abstract: This research aims to develop and characterize a protein drug delivery system in agarose-glucan complex. The complex was produced by sonicating the mixture of agarose-glucan components and a protein in liquid paraffin with Sonics Vibracell Processor adapted from the method of Nuo Wang et all 1997. Etanercept, an anti-tumor necrosis factor-alpha (anti-TNF-α), was used as a model protein drug which was successfully encapsulated into agarose-glucan complex system. This protein can neutralize the TNF-α, a pro-inflammatory cytokine that plays a pivotal role in regulating the inflammatory response in rheumatoid arthritis (RA) and is well-known as mediator worsening RA pathogenesis. The prepared agarose-glucan complex possesses a range of sizes, from 30 to 150 nm, dissolves well within the range of pH buffer from 5.2 to 6.2 with an average protein encapsulating efficiency up to 74.4%, and can release up to 50% of protein after 40.3 hours. This research is the basis for developing nanogel-sized targeted drug delivery in RA treatment. Keywords: Agarose gel, agarose microspheres, glucan, emulsification cooling, rheumatoid arthritis. References [1] N. Wang and X.S. Wu, Preparation and Characterization of Agarose Hydrogel Nanoparticles for Protein and Peptide Drug Delivery. Pharmaceutical Development and Technology 2(2) (1997) 135-142. [2] Zhi-gang Jing, Chun-yu YANG, Chun-li YANG, Hailing Liu, Shuo Yang: Preparation of Homogeneous and Controllable Agarose Micro-beads. Advances in Sciences and Engineering (2016). [3] Nuo Wang, Xue Shen Wu, A novel approach to stabilization of protein drugs in poly(lactic-co-glycolic acid) microspheres using agarose hydrogel. International Journal of Pharmaceutics 166(1) (1998) 1-14. [4] P.R. Taylor, S.V. Tsoni, J.A. Willment, K.M. Dennehy, M. Rosas, H. Findon, K. Haynes, C. Steele, M. Botto, S. Gordon, Dectin-1 is required for beta-glucan recognition and control of fungal infection. Nature immunology 8(1) (2007) 31-38. [5] M. Kanke, E. Tanabe, H. Katayama, Y. Koda, H. Yoshitomi, Application of curdlan to controlled drug delivery. III. Drug release from sustained release suppositories in vitro. Biological and Pharmaceutical Bulletin 18(8) (1995), 1154-1158. [6] Beom Soo Kim, In Duck Jung, Jong Sik Kim, Jung-heon Lee, In Young Lee, Kyung Bok Lee, . Biotechnology letters 22(14) (2000), 1127-1130. [7] E.H. Choy and G.S. Panayi, Cytokine pathways and joint inflammation in rheumatoid arthritis, New England Journal of Medicine 344(12) (2001) 907-916. [8] C.Tetta, G. Camussi, V. Modena, C. Di Vittorio, C. Baglioni, Tumour necrosis factor in serum and synovial fluid of patients with active and severe rheumatoid arthritis. Annals of the Rheumatic Diseases, 49(9) (1990) 665-667. [9] J. F. Fries, Current treatment paradigms in rheumatoid arthritis, Rheumatology 39, (2000) 30–35. [10] I. H. Tarner, U. Müller-Ladner. Drug delivery systems for the treatment of rheumatoid arthritis. Expert opinion on drug delivery 5(9) (2008) 1027-1037. [11] Chen Y.F., P. Jobanputra, P. Barton, S. Jowett, S. Bryan, W. Clark, A. Fry-Smith, A. Burls, A systematic review of the effectiveness of adalimumab, etanercept and infliximab for the treatment of rheumatoid arthritis in adults and an economic evaluation of their cost-effectiveness. Health Technol Assess 10(42) iii-iv, xi-xiii (2006), 1-229. [12] P.S. Zehra Kaymakcalan, Sahana Bose, Comparisons of affinities, avidities, and complement activation of adalimumab, infliximab, and etanercept in binding to soluble andmembrane tumor necrosis factor, Clinical Immunology 2009. [13] Y. Tanaka, Current concepts in the management of rheumatoid arthritis. Korean J Intern Med 31(2) (2016) 210-8. [14] Eun Ju Lee, Joong Kon Park, Saeed A. Khan, Kwang-Hee Lim, Preparation of Agar Nanoparticles by W/O Emulsification.Journal of Chemical Engineering of Japan, 44(7) (2011) 502–508. [15] Jaleh Varshosaz, Mohammad Reza Zaki, Mohsen Minaiyan, Jaafar Banoozadeh, Preparation, Optimization, and Screening of the Effect of Processing Variables on Agar Nanospheres Loaded with Bupropion HCl by a D-Optimal Design, BioMed Research International 2015, vol. 2015, Article ID 571816, 13 pages, 2015. https://doi.org/10.1155/2015/571816.